2019
DOI: 10.1186/s12933-019-0911-4
|View full text |Cite
|
Sign up to set email alerts
|

Successful revascularization versus medical therapy in diabetic patients with stable right coronary artery chronic total occlusion: a retrospective cohort study

Abstract: Background The territory of the right coronary artery (RCA) is smaller than that of the left anterior descending artery. Previous studies have reported conflicting results when considering whether stable RCA-chronic total occlusion (CTO) should be reopened. The coexistence of diabetic and coronary artery diseases represents a severe situation. Therefore, we aimed to determine if stable RCA-CTO in diabetic patients was necessary to be reopened. To our knowledge, no studies have focused on this topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Moreover, successful PCI was associated with better cardiac survival in elderly especially when complete revascularization is achieved [27]. Recently, Yunfeng et al also reported that successful revascularization of CTO of stable right coronary artery either by PCI or bypass graft showed significant reduction of all-cause mortality (HR: 0.429, 95% CI 0.269-0.682) [28]. These evidences highlighted the importance of complete revascularization.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, successful PCI was associated with better cardiac survival in elderly especially when complete revascularization is achieved [27]. Recently, Yunfeng et al also reported that successful revascularization of CTO of stable right coronary artery either by PCI or bypass graft showed significant reduction of all-cause mortality (HR: 0.429, 95% CI 0.269-0.682) [28]. These evidences highlighted the importance of complete revascularization.…”
Section: Discussionmentioning
confidence: 96%
“…[27] Recently, Yunfeng Y et al also reported that successful revascularization of CTO of stable right coronary artery either by PCI or bypass graft showed signi cant reduction of all-cause mortality (HR: 0.429, 95% CI: 0.269 -0.682). [28] These evidences highlighted the importance of complete revascularization. Bene t of recanalization of CTO may be more pronounced in patients with elderly and poor left ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Recently, Yunfeng Y et al also reported that successful revascularization of CTO of stable right coronary artery either by PCI or bypass graft showed signi cant reduction of all-cause mortality (HR: 0.429, 95% CI: 0.269-0.682). [21] These evidences highlighted the importance of complete revascularization. Bene t of recanalization of CTO may be more pronounced in patients with elderly and poor left ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 99%